Upper gastrointestinal bleeding in hospital inpatients: the role of antithrombotic drugs. Issue 1066 (3rd June 2014) - Taha, Ali S; Kelly, Claire; McCloskey, Caroline; Craigen, Theresa; Angerson, Wilson J
Abstract: Background: Critically ill patients are considered to be most at risk from developing non-variceal upper gastrointestinal bleeding (NVGIB) while in hospital. The increasing prescription of low-dose aspirin and other antithrombotic drugs for protection against thromboembolism to many patients admitted to hospital may increase the vulnerability of a wider group to NVGIB. Objective: This study compares two groups of patients with NVGIB: group I, inpatients cared for outside the intensive care unit; and group II, patients admitted with this condition, while considering the use of antithrombotic drugs. Methods: We identified all patients who developed NVGIB in the two calendar years between 2008 and 2009 and compared group I with group II while taking into account their clinical details including Rockall scores and drug usage. Results: Compared with group II (n=274), group I (n=96) were older (median age of 77 years vs 68; p<0.001), had fewer males (45.8% vs 60.6%; p=0.016), higher prevalence of cardiovascular disease (52.1% vs 29.2%; p<0.001), more patients with complete Rockall score ≥3 (84.4% vs 66.7%; p=0.001) and more patients treated with aspirin or other antithrombotic drugs (64.6% vs 44.5%; p=0.001). After adjustment for age and sex, group I were still significantly more likely to be taking antithrombotic drugs than group II (OR (95% CIs), 2.15 (1.25 to 3.68); p=0.006). The endoscopic abnormalities in more than 80% of patients included erosive oesophagitis, gastric or duodenal ulcers or erosions. Conclusions: Subjects who develop NVGIB as inpatients have higher Rockall scores are mainly older females with cardiovascular disease and using antithrombotic drugs. Secondary care clinicians should be mindful of this at-risk group of patients and consider giving them prophylactic antiulcer therapy.